The new dicyanoruthenium(iii) building block with 2′-hydroxyacetophenone imine for heterobimetallic complexes. Issue 113 (4th November 2015) - Ru, Jing; Zong, Tian-Xiang; Ge, Jing-Yuan; Yao, Min-Xia; Zuo, Jing-Lin
Abstract : Five one-dimensional heterobimetallic chains based on the new dicyanoruthenium(iii ) complex, trans -(Ph4 P)[Ru(L)2 (CN)2 ] (L = 2′-hydroxyacetophenone imine), are synthesized and structurally characterized. Magnetostructural correlation for these compounds is discussed. Abstract : A new ruthenium(iii )-based building block, trans -(Ph4 P)[Ru III (L)2 (CN)2 ] (L = 2′-hydroxyacetophenone imine), has been synthesized and characterized. Reactions of this building block with different Mn III Schiff base (SB) complexes, [Mn(SB)(H2 O)2 ]ClO4, result in 1-D zigzag chain complexes, [Ru III (L)2 (CN)2 Mn III (SB)] n (SB = salen, 1 ; salcy, 2 ; nappa, 4 ; napcy, 5 ), respectively. X-ray crystallographic studies reveal that each of the Mn III centers has a distorted octahedral environment, while complex3 possesses a single cationic chain structure consisting of [Cu(chxn)2 ][Ru(L)2 (CN)2 ] n units and their corresponding [Ru(L)2 (CN)2 ] − anions. Compounds1–3 exhibit antiferromagnetic coupling between the Ru III and Mn III /Cu II centers, whereas4 and5 reveal ferromagnetic coupling between the Ru III and Mn III centers through the cyano bridges. Furthermore, magneto-structural correlation for some typical cyano-bridged heterobimetallic Ru III –Mn III /Cu II compounds is discussed.